Primary Atrophic Rhinitis: A Clinical Profile, Microbiological and Radiological Study - Bist, Sampan S. (International Scholarly Research Network, 2012)
Background. The objective of this prospective study was to evaluate the clinical profile, microbiological flora and radiological features in primary atrophic rhinitis patients and to identify their association with the etiology of primary atrophic rhinitis. Study design. Prospective case study. Materials and methods. Patients with primary atrophic rhinitis over a two years period were included in the study. Complete blood count, total protein and microbiological analysis from nasal swab were done to evaluate iron deficiency anemia, nutritional status and identification of the pathogenic bacteria respectively. Radiological evaluation was done to study the radiological features of primary atrophic rhinitis. Observations. Ninety cases of primary atrophic rhinitis were studied. The most common symptom was nasal crusting. Nasal crust, odour and atrophy of mucosa were the most consistent finding. Nasal myiasis was found in 26.6% cases. The nasal mucociliary clearance time was markedly increased. On investigation there were low value of hemoglobin and total protein in 46.6% and 25.5% patients, respectively. Pseudomonas aeruginosa (37%) was the commonest organism isolated from culture. On radiological evaluation evidence of different grade of sinusitis was seen in 87.7% case. Conclusion. The present study suggested that certain bacterial infections, anemia, poor nutrition and hereditary factor may contribute significantly to the etiology of primary atrophic rhinitis.